Agitation Predicts Response of Depression to Botulinum Toxin Treatment in a Randomized Controlled Trial - Wollmer, Marc A.; Kalak, Nadeem; Jung, Stephanie; DeBoer, Claas; Magid, Michelle; Reichenberg, Jason S.; Brand, Serge; Holsboer-Trachsler, Edith; Kruger, Tillmann H. (Frontiers in Psychiatry, 2014)
In a randomized, controlled trial (n=30) we showed that botulinum toxin injection to the glabellar region produces a marked improvement in the symptoms of major depression. We hypothesized that the mood-lifting effect was mediated by facial feedback mechanisms. Here we assessed if agitation, which may be associated with increased dynamic psychomotor activity of the facial musculature, can predict response to the treatment. To test this hypothesis we re-analyzed the data of the scales from our previous study on a single item basis and compared the baseline scores in the agitation item (item 9) of the Hamilton Depression Rating Scale (HAM-D) between responders (n=9) and participants who did not attain response (n=6) among the recipients of onabotulinumtoxinA (n=15). Results: Responders had significantly higher item 9 scores at baseline (1.56+0.88 vs. 0.33+0.52, t(13)=3.04, d=1.7, p=0.01), while no other single item of the HAM-D or the Beck Depression Inventory was associated with treatment response. The agitation score had an overall precision of 78% in predicting response in a receiver operating characteristic (ROC) analysis (area under the curve, AUC=0.87). These data provide a link between response to botulinum toxin treatment with a psychomotor manifestation of depression and thereby indirect support of the proposed facial feedback mechanism of action. Moreover, it suggests that patients with agitated depression may particularly benefit from botulinum toxin treatment.